Design and Implementation of a Smart Energy Management System (SEMS) for Food Truck DC Loads in Off-Grid Photovoltaic (OGPV) - Suhaimi, Harith Aiman; Salimin, Suriana (Journal of Electronic Voltage and Application, 2025)
Mobile food trucks need diesel generators or gasoline to produce power to operate essential appliances. This leads to increased fuel expenditures, emissions, and noise pollution, which are harms to the environment, as well as customers’ and employees’ experience. To reduce these burdens, this project was to design and develop a Smart Energy Management System (SEMS) to replace the need for a diesel generator by integrating it with an Off-Grid Photovoltaic (OGPV) to power DC loads more efficiently. An energy demand analysis was conducted on four food trucks located in Kuala Lumpur; the data collected from the appliances was analyzed to create an Excel-based tool that allowed us to determine the optimal sizes of PV panels, batteries, and MPPT charge controllers that provided a two-day autonomy (for cloudy days). The tools were validated using the PVsyst software and the analysis showed an average load demand error of lower than 0.4% which validated the tool’s effectiveness. A SEMS prototype with an ESP32 microcontroller was built that utilized voltage, current, light, and rain sensors, and the prototype was able to automate lighting control and monitor real-time data using an LCD display and Arduino IoT Cloud. Testing in the day, night, and rain proved the system’s capacity to manage energy very efficiently along with reliable operations and the ability to adapt to variable environments. To summarize, the integrated SEMS-OGPV system provides a real-world user outcome as a practical, sustainable, and scalable energy solution for mobile food operations considering the accurate sizing, optimized efficiencies, and greater environmental considerations.